Caught in transition: changes in brachyuran diversity following mangrove encroachment into saltmarshes at a southern distribution limit - Katharoyan, Chaitanya; Rajkaran, Anusha; Peer, Nasreen (Frontiers in Marine Science, 2024)
Mangroves are expanding polewards due to global change, often encroaching into adjacent temperate saltmarshes. In both vegetated ecosystems, brachyurans are responsible for ecological processes and functions such as nutrient cycling and sediment bioturbation. South African mangroves occur at a latitudinal limit and are establishing further south due to past planting events and global change, making these ideal study systems for the effects of mangrove expansion and encroachment. Here, we investigated the effect of mangrove encroachment on brachyuran community composition at two saltmarsh sites with planted mangrove stands of different ages. Transects were laid perpendicular to each estuary where three habitat types were demarcated (mangrove, ecotone, saltmarsh). Sediment samples were collected for analyses and quadrats were used to measure pneumatophore density, saltmarsh cover, and brachyuran abundance and diversity. We found that brachyuran community structure at each site has significantly changed over seven years, with two mangrove-associated fiddler crab species, Tubuca urvillei and Paraleptuca chlorophthalmus, now recorded at the younger planted site, indicating a new southern distributional limit. Community structure was also significantly different amongst habitat types (p < 0.05) with Parasesarma catenatum dominating saltmarshes while Danielella edwardsii was more prominent in mangroves. However, community composition did not differ significantly between the two (differently aged) sites (p > 0.05). Pneumatophore density had a proportional relationship with crab abundance, diversity and richness, while saltmarsh cover had an inversely proportional relationship with crab abundance, diversity and richness. It is likely that as mangroves continue to expand into saltmarshes, more mangrove-associated species will move into saltmarshes, potentially altering ecosystem processes in this unique habitat.